Organic Reactions 2011
DOI: 10.1002/0471264180.or018.03
|View full text |Cite
|
Sign up to set email alerts
|

The Reactions of Diazoacetic Esters with Alkenes, Alkynes, Heterocyclic and Aromatic Compounds

Abstract: After the first unsuccessful attempt of Curtius in 1884 to affect the reaction of ethyl diazoacetate with toluene other researchers studied the reaction. Later, Buchner and Curtius treated several aromatic, olefinic, and acetylenic compounds with diazoacetic esters to form cyclopropanes. Since then the reactions of diazoacetates with various unsaturated compounds have been studied. The carbalkoxy carbenes are of interest since they are believed to be intermediates in higher temperature thermal and photochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 413 publications
0
4
0
Order By: Relevance
“…In this report the thermolysis of an α-bromodiazoketone was successfully employed in an intramolecular cyclopropanation reaction [62]. Historically, the thermolysis of diazocarbonyl compounds has been carried out under reflux [6366], although examples of low temperature and ambient temperature thermolysis can be found in the case of more labile diazo compounds [14,2223 67]. Recent examples of thermolyses of diazocarbonyl compounds, include the preparation of arylcyclopropanes (cyclopropanation) and α-arylamino esters (N–H insertion) by thermolysis of aryldiazoacetates in trifluorotoluene under reflux [6869].…”
Section: Discussionmentioning
confidence: 99%
“…In this report the thermolysis of an α-bromodiazoketone was successfully employed in an intramolecular cyclopropanation reaction [62]. Historically, the thermolysis of diazocarbonyl compounds has been carried out under reflux [6366], although examples of low temperature and ambient temperature thermolysis can be found in the case of more labile diazo compounds [14,2223 67]. Recent examples of thermolyses of diazocarbonyl compounds, include the preparation of arylcyclopropanes (cyclopropanation) and α-arylamino esters (N–H insertion) by thermolysis of aryldiazoacetates in trifluorotoluene under reflux [6869].…”
Section: Discussionmentioning
confidence: 99%
“…The Buchner ring expansion reaction is used to assemble 1,3,5-cycloheptatrienes. It involves the cyclopropanation of an aromatic ring by a carbene (generated from a diazo compound with the aid of light, heat, or a metal catalyst), giving rise to a norcaradiene, which is in equilibrium with the corresponding cycloheptatriene through a 6-electron disrotatory electrocyclic process (valence tautomerism, Scheme ). …”
Section: Construction Of 3-membered Rings Catalyzed By Goldmentioning
confidence: 91%
“…Since a study of copper dust catalyzed decomposition of ethyl diazoacetate (EDA) in 1906 was reported (10), copper bronze catalyzed cyclopropanations with diazo compound decomposition have been developed gradually. Although the insoluble copper has been a popular catalyst for cyclopropanation of olefins for more than six decades (11), their many limitations, such as high catalyst loading, elevated temperature, and moderate yield of cyclopropane, have generally not been surmounted.…”
Section: Diazo Compounds Decomposition In the Presence Of Alkenesmentioning
confidence: 99%